Magnetic drug-loaded microbubbles for treating lower limb venous thrombosis under controllable rotating magnetic field - Huang, Yu-Ming; Liu, Cheng-Rang; Xu, Yi-Qi; Cao, Chao; Huang, Zhen-Gan; Fei, Hong-Wen; Huang, Yue-Shan (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study aimed to develop a poly (lactic-co-glycolic acid) (PLGA)-based magnetic loaded iron oxide (Fe3O4) and single-chain urokinase-type plasminogen activator (proUK) for enhancing thrombolysis under a controlled rotating magnetic field, specifically targeting acute lower limb venous thrombosis.BackgroundAcute thrombotic disorders are significant health threats, however, the exploration of magnetic actuation as a treatment for acute thrombosis has been limited.MethodsMagnetic microbubbles were prepared using a double emulsion method, loaded with Fe3O4 nanoparticles and proUK. The microbubble characteristics were analyzed through chemical, physical, and biological related technologies.ResultsFe3O4 nanoparticle loading was confirmed by X-ray diffraction, and the encapsulation efficiency of the magnetic microbubbles was determined using an ELISA kit and colorimetric assay, reaching a maximum of 56.65% at a proUK concentration of 7.5 mg/mL. Thrombolysis efficiency was significantly enhanced under a rotating magnetic field of 1.5 mT and 6 Hz frequency, achieving up to 25% lysis rate in vitro, markedly higher than control conditions. Furthermore, in vivo experiments using a rabbit model of hindlimb venous thrombosis validated the efficacy of this approach, with Color Doppler Flow Imaging showing restored blood flow and elevated D-dimer levels indicating effective thrombus dissolution.ConclusionThis novel magnetic drug delivery system, combined with a rotating magnetic field, demonstrates excellent thrombolysis efficiency and presents a promising and safe therapeutic strategy for acute venous thrombosis.